2019
DOI: 10.1080/17508975.2019.1674625
|View full text |Cite
|
Sign up to set email alerts
|

Development and field testing of a multi-dimensional tool for benchmarking knowledge worker productivity

Abstract: The impact of indoor environmental quality on human health and wellbeing has been widely documented, as has its impact on worker productivity in settings such as education, healthcare, and manufacturing. In the knowledge worker context, however, there is limited consensus on agreed metrics for productivity measurement, leading to a paucity of research regarding the impact of specific realworkplace interventions on worker performance. This paper presents an organizational benchmarking and evaluation tool to per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Also, the objective of the study was justified that usability-based benchmarking measures largely mediates the relationship between portfolio optimization and client satisfaction in the technology sector of real estate management in India with the value of VAF (97%) greater than 80%. Fernandes et al. (2019) found that optimal energy efficiency of a building (energy performance benchmarks) can be achieved through an integrated design process (IDP), with stakeholders involved from the beginning of building modelling (design phase) and during measurement and verification (operations phase).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the objective of the study was justified that usability-based benchmarking measures largely mediates the relationship between portfolio optimization and client satisfaction in the technology sector of real estate management in India with the value of VAF (97%) greater than 80%. Fernandes et al. (2019) found that optimal energy efficiency of a building (energy performance benchmarks) can be achieved through an integrated design process (IDP), with stakeholders involved from the beginning of building modelling (design phase) and during measurement and verification (operations phase).…”
Section: Discussionmentioning
confidence: 99%
“…The authors declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper. -Satisfaction with absence/presence plants - [115,121,167,192] -Number of plants - [48,59,92,121,191] -Connectedness to nature - [108,193,194 *Indicates objective measures. - [95,124] Flourish model High-quality physical work environment stimulates individuals' flourishing; promotes an optimal state of human functioning, with high mental well-being and health.…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%
“…When enterprises evaluate knowledge-based employees, the specific content will change according to different assessment purposes and assessment scope (Fernandes et al, 2019;Rajabpour and Chartab Moghadam, 2019). Considering the particularity of knowledge-based talents, multi-layer fuzzy comprehensive evaluation method is selected to improve the accuracy of talent management evaluation.…”
Section: Construction Of Talent Management Model In Knowledge-based Organizationmentioning
confidence: 99%